Hubungan Mekanisme Koping dengan Stres Pasien TB Paru di Rumah Sakit Paru Jember - Lie Liana Fuadiati; Erti Ikhtiarini Dewi; Enggal Hadi K (UPT Percetakan dan Penerbitan Universitas Jember, 2019)
Tuberculosis is an infectious disease which can cause negative stigma from the community leading to stress of patient. Stress in tuberculosis patients may also be caused by the length of medication period as well as the side effect of the medicine. When stress affects the medication taken by the patients, the stress management is highly needed. It can be done by identifying the coping mechanism. The objective of this study was to analyze the correlation between the coping mechanism and the stress of the tuberculosis patients at the Paru Hospital, Jember. The design of this study was analytical correlational by using cross sectional approach. The population of this study was 145 patients. The sampling was 84 patients obtained by using consecutive sampling technique. The result of data analysis by Spearman correlation revealed the p-value of 0.00; r:- 0.529. This indicated that there is a correlation between the coping mechanism and the stress of the tuberculosis patients at the Paru Hospital Jember. It is suggested that nurses should pay attention to improve the patient’s coping mechanism by providing education and counseling about tuberculosis disease and stress management. Stress management or coping can help patients to manage stress and further may complete the medication.